The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/ijc.11681
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I antigen processing pathway defects, ras mutations and disease stage in colorectal carcinoma

Abstract: Colorectal tumorigenesis has been associated with the progressive acquisition of a variety of genetic alterations. These include mutations of the Ki-ras proto-oncogene in codons 12 and 13, which account for 85% of genetic changes in colorectal cancer. In murine in vitro models of oncogenic transformation, an association between ras-mediated transformation and downregulation of different components of the MHC class I antigen processing machinery (APM) has been described. In order to investigate whether this ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
80
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 45 publications
10
80
0
Order By: Relevance
“…8,9 Loss of tapasin expression is a frequent event that has been reported in a wide variety of human cancers, including malignant melanoma, head and neck squamous cell carcinoma (HNSCC), renal cell carcinoma, colorectal carcinoma, glioblastoma, lung carcinoma, and neuroblastoma. [10][11][12][13][14][15][16][17][18] Notably, tapasin expression associated with intratumoral T-cell infiltration has been reported as a prognostic marker of patient survival in ovarian carcinoma, HNSCC, glioblastoma, and colorectal carcinoma. 12,13,[19][20][21] It is also reported that loss of tapasin is more frequent among the other antigen-processing machinery (APM) components, strongly suggesting its central role in escape from CTL immune surveillance to tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Loss of tapasin expression is a frequent event that has been reported in a wide variety of human cancers, including malignant melanoma, head and neck squamous cell carcinoma (HNSCC), renal cell carcinoma, colorectal carcinoma, glioblastoma, lung carcinoma, and neuroblastoma. [10][11][12][13][14][15][16][17][18] Notably, tapasin expression associated with intratumoral T-cell infiltration has been reported as a prognostic marker of patient survival in ovarian carcinoma, HNSCC, glioblastoma, and colorectal carcinoma. 12,13,[19][20][21] It is also reported that loss of tapasin is more frequent among the other antigen-processing machinery (APM) components, strongly suggesting its central role in escape from CTL immune surveillance to tumors.…”
Section: Introductionmentioning
confidence: 99%
“…12,13,[19][20][21] It is also reported that loss of tapasin is more frequent among the other antigen-processing machinery (APM) components, strongly suggesting its central role in escape from CTL immune surveillance to tumors. 15,22 Impaired CTL responses against tapasin-deficient cells have been well established in mouse models. 8,9 In human cases, loss of tapasin alters the peptide repertoire presented by HLA-B Ã 2705 and results in a decrease in alloreactive CTL responses.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, reduced expression of antigen presentation pathway components restricts the flow of peptide loaded MHC class I molecules to the cell surface [15]. Expression of oncogenic RAS has previously been linked with the reduced expression of antigen presentation pathway components in mouse cells and in human tumour tissue [16][17][18] (and reviewed in [3]). These components include the transporter of antigen processing (TAP) and the TAP-associated molecule, tapasin, which are required for efficient delivery of antigenic peptides into the endoplasmic reticulum (ER) [14].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that targeted inactivation of oncogenic RAS may restore expression of MHC class I molecules to the cell surface and help to boost T cell recognition. However, there are conflicting reports on the association between RAS mutations and antigen presentation in human tumours [18][19][20], indicating that functional studies are required. We have analysed the role of mutant RAS oncogenes in regulating the expression of MHC class I molecules and in determining the recognition of RAS mutant tumours by cytotoxic lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Interferon (IFN)-g-inducible genes, for instance the proteasome subunits, low molecular weight proteins (LMP)2, LMP7, LMP10 and the antigen transporters, transporters associated with antigen processing (TAP) 1 and TAP2, appear to be obligatory for the T-cell target recognition of tumors (Driscoll et al, 1993;Gaczynska et al, 1993;Belich et al, 1994;Momburg et al, 1994a, b;Groettrup et al, 1997;Seliger et al, 2000). Many tumor cells unfortunately have lost this ability, thereby evading CTL-mediated immune surveillance and elimination (Garrido et al, 1997;Seliger et al, 2000;Dunn et al, 2002;Miyagi et al, 2003;Atkins et al, 2004). The defective antigen presentation by MHC class I is attributed to the downregulation of several genes required for antigen processing or presentation, such as TAP1 and TAP2, and LMP2 and LMP7 (Singal et al, 1996;Dovhey et al, 2000;Cabrera et al, 2003).…”
Section: Introductionmentioning
confidence: 99%